Cooling of electronic devices: Nanofluids contribution. (25th December 2017) - Colangelo, G.; Favale, E.; Milanese, M.; de Risi, A.; Laforgia, D.
Highlights: The application of nanofluids for cooling electronic devices is analyzed. Nanofluids as heat transfer fluids improve thermal performance of heat exchangers. The most used nanoparticles in this field are Al2 O3 . In literature, there are no data about the problem of clogging and how to face it. Abstract: Cooling of electronic devices is one of the main challenge of new generation technology. The extreme miniaturization has high benefits, but the heat to be dissipated per unit of surface increases in uncontrolled way. In this paper the application of a new generation of heat transfer fluids, nanofluids, to electronic devices is analyzed. Even if the use of nanofluids is not still common, there are many papers that deal with this topic, reporting both experimental and theoretical results. The development of this technology could be one of the key elements that could give an important impulse to further miniaturization of electronic devices and at the same time increase their energy efficiency.